Impact on Quality of Life of Seton Placing in Perianal Crohn's Disease - Angriman, Imerio; Tomassi, Monica; Ruffolo, Cesare; Bordignon, Giovanni; Saadeh, Luca; Gruppo, Mario; Pucciarelli, Salvatore; Bardini, Romeo; Scarpa, Marco (Frontiers in Surgery, 2022)
Currently, in perineal Crohn’s disease [CD] it is placed to guarantee a constant drainage and prevent septic complication while biologic therapy is ongoing. This study aimed to assess the long-term quality of life after surgery for perineal CD. Data of 65 consecutive CD and non CD patients operated on from 2014 to 2019 for perianal fistula or abscess were retrieved. Forty-three had CD and 14 of them had a seton placed during surgery and they kept it on while they had anti-TNF-alpha therapy. Patients were interviewed with the Cleveland Global Quality of Life [CGQL] and SF-12 quality of life questionnaires. Disease activity was defined as Harvey-Bradshaw Index [HBI] and Perianal Disease Activity Index [PDAI]. Comparisons between groups were carried out with non-parametric tests multiple regression models were used to assess predictors of quality of life. The total CGQL score and SF-12 mental component score [MCS] were significantly higher [and thus better] in the seton group than in patients treated without seton. On the contrary, SF-12 physical component score [PCS] was not different between the two groups. HBI was significantly better in patients in the seton group. At multivariate analysis, seton placement and HBI confirmed to be independent predictors of long-term SF-12 mental component score [MCS] while only HBI confirmed to be a predictor of total CGQL score. Seton placing during anti-TNF-alpha therapy is independently associated to a better MCS. Unexpectedly, this device, instead to cause a psychological distress, seem to assure patients during their biologic therapy providing psychological benefit beyond the mere medical effect.